Stakeholder Forum of the Sub-sector Working Group on Irrigation (SSWG-IR): the opportunities for solar-powered irrigation in Lao PDR - Inphonephong, Souphalack; Vongxay, V.; Bounnavong, K.; Dubois, Mark (International Water Management Institute, 2024)
This report summarizes the 2024 second semiannual Stakeholder Forum of the Sub-sector Working Group on Irrigation (SSWG-IR), held in Vientiane Capital, Lao PDR, on October 14, 2024. Organized by the Department of Irrigation (DOI) under the Ministry of Agriculture and Forestry (MAF), and supported by the Asian Development Bank (ADB) through the International Water Management Institute (IWMI), the forum gathered over 80 participants from government, academia, development organizations, farmer groups, and enterprises.